117k views
0 votes
Solve the system using substitution

Solve the system using substitution-example-1

2 Answers

6 votes

Answer:

No solution

Explanation:

Given equations are 2x-y=-6 and -4x+2y=-9.

Now we need to solve that system of equation using substitution method.

solve 2x-y=-6 for y

2x-y=-6

-y=-6-2x

y=6+2x

Plug this value of y into other equation -4x+2y=-9

-4x+2(6+2x)=-9

-4x+12+4x=-9

12=-9

Which is a false equation.

Hence there is no solution to the given system.

User Bugmagnet
by
4.6k points
3 votes

Answer: Option B

No solutions

Explanation:

We have the following system of equations


2x - y = -6 (1)


-4x + 2y = -9 (2)

To solve the system using the substitution method, solve the first equation for the variable y


y=2x+6

Now substitute the value of y in the second equation


-4x + 2(2x +6) = -9


-4x + 4x +12=-9


12=-9

2 is not equal to -9, the system is inconsistent. The system has no solution